Analysis of Climate-Related Disclosures in Telkom's 2024 Sustainability Report According to Ifrs S2 Requirements - Fransiskus Nicolas; Chaerul Djakman (Eduvest - Journal of Universal Studies, 2026)
The implementation of the global IFRS S2 standard regarding climate-related disclosures presents new challenges for corporate reporting transparency in developing economies. This study aims to evaluate the readiness of climate-related disclosures of PT Telkom Indonesia (Persero) Tbk in its 2024 Sustainability Report based on IFRS S2 requirements. This research employs a qualitative approach using content analysis of public corporate documents, utilizing the IFRS S2 disclosure checklist instrument, which covers four main pillars: governance, strategy, risk management, and metrics and targets. The findings indicate that PT Telkom Indonesia demonstrates a partial level of readiness in adopting the standard. Mature readiness is identified in the governance and risk management pillars, where climate change issues have been effectively integrated into board oversight structures and enterprise risk management frameworks. However, material gaps are found in the strategy and metrics pillars, particularly regarding the absence of quantified financial effects of climate risks on the company’s financial position, the lack of quantitative climate scenario analysis, and the incomplete Scope 3 GHG emissions inventory. The study concludes that while institutional foundations are established, the company needs to prioritize the development of financial impact models and the expansion of supply chain data to achieve full compliance in the future.